Prosomeric organization of the hypothalamus in an elasmobranch, the catshark Scyliorhinus canicula - Santos-Durán, Gabriel N.; Menuet, Arnaud; Lagadec, Ronan; Mayeur, Hélène; Ferreiro-Galve, Susana; Mazan, Sylvie; Rodríguez-Moldes, Isabel; Candal, Eva (Frontiers in Neuroanatomy, 2015)
The hypothalamus has been a central topic in neuroanatomy because of its important physiological functions, but its mature organization remains elusive. Deciphering its embryonic and adult organization is crucial in an evolutionary approach of the organization of the vertebrate forebrain. Here we studied the molecular organization of the hypothalamus and neighboring telencephalic domains in a cartilaginous fish, the catshark, Scyliorhinus canicula, focusing on ScFoxg1a, ScShh, ScNkx2.1, ScDlx2/5, ScOtp, and ScTbr1 expression profiles and on the identification α-acetylated-tubulin-immunoreactive (ir), TH-ir, 5-HT-ir, and GFAP-ir structures by means of immunohistochemistry. Analysis of the results within the updated prosomeric model framework support the existence of alar and basal histogenetic compartments in the hypothalamus similar to those described in the mouse, suggesting the ancestrality of these subdivisions in jawed vertebrates. These data provide new insights into hypothalamic organization in cartilaginous fishes and highlight the generality of key features of the prosomeric model in jawed vertebrates.